Dampak Penularan Krisis Global terhadap Aliran Investasi Asing di Indonesia - Enggal Sriwardiningsih (Bina Nusantara University, 2010)
Global crisis and Greece crisis have potential contagion effect to emerging market by two main ways, which are export emerging market countries decrease to developed countries and financial crisis developed countries made foreign direct investment bring back their financial from emerging countries because of lack of capital. But Indonesia economy has good conduct to support investment by his regulation, so it make high expectation opportunities to foreign direct investment come to Indonesia. The problem is how is short–term capital change becoming long-term foreign direct investment that makes Indonesia economy can sustainable growth economy. Government control the rate of banks, inflation and fiscal stimulus in Indonesia dynamic condition perhaps Indonesia economy potential propose his target growth according his expectation for 5 years later (2010-2014).